The role of schools within initial teacher education in England: an exploration of the shifting policy focus over the past 50 years - Mutton, T; Burn, K; Molway, L (Taylor and Francis, 2024)
Looking back to the very first issue of the Journal of Education for Teaching, it is clear that initial teacher education (ITE) was, at the time, undergoing significant change and has, in fact, been subject to political scrutiny in each of the intervening decades. Our paper traces key policy moments over the past 50 years in England, examining specifically those policies which have had implications for the role of schools and school-based teacher educators within ITE programmes. Our interest is in the broader context that has informed ITE policy-making, the content of those policies, and the implications for the role of schools. We go on to discuss how the concept of ITE partnership working has evolved over this period and then consider the pedagogic role that schools can play in the education of teachers, including the role of school-based mentors. Finally, we consider the potential impact on practice of the most recent set of ITE reforms in England.